Recruitment Process Outsourcing impact on Human resource Planning and Development in Pharmaceutical Sector. - Tank, Sunita; Singh Chowhan, Prof. (Dr.) Sudhinder (IJRDO - Journal of Business Management, 2017)
The growing concept of recruitment outsourcing has its impact on every aspect of business. Cost reduction with profitability, growth and business expansions was high on company’s agenda. Many companies started doing cost cutting during economic downturn and tough market competition and thinking to outsource some of its core functions, Greer,Youngblood, and Gray (1999). In order to address the demand of lowering the recruitment cost, human resource planned to outsource it in order to manage this HR services with effective HR planning and development within an organization. Downsizing and strict competition also meant that the HR is also under continuous pressure to demonstrate incurred cost, both efficiently and effectively (Roberts, 2001). HR professionals’ stated that an effective and efficient culture of recruitment, selection and positioning of talent has a major impact on survival, growth and development of an organization; Ofori&Aryeetey, 2011. Ongori 2010, recruitment and selection practices are the key factors to ensure the success and growth of an organization. However the typical reasons to outsource recruitment, apart from cost reduction were to seek specialize HR services and expertise and concentration of internal HR specialists on more of strategic role in talent management in the business. In this regard, the following paper is undertaken to examine the impact of recruitment process outsourcing on the human resource planning and development as a whole